Free diffusion to and from the inner nuclear membrane of newly synthesized plasma membrane glycoproteins (The Rockefeller University Press, 1987)
Sindbis virus-infected baby hamster kidney (BHK) cells were analyzed by thin section fracture-label. Specific immunolabel with antiviral glycoprotein antibodies was used in conjunction with colloidal gold- conjugated protein A. As we previously reported (Torrisi, M. R., and S. Bonatti, 1985, J. Cell Biol., 101:1300-1306), Sindbis transmembrane glycoproteins are present in the inner nuclear membrane as well as in the outer nuclear membrane, endoplasmic reticulum, Golgi stacks and vesicles, and plasma membranes. Viral glycoproteins located on the inner nuclear membrane resemble those present on the outer membrane in terms of amount, distribution, and preferential partition after fracture. We show in this paper that Sindbis glycoproteins after treatment with cycloheximide are removed from the inner nuclear membrane with the same kinetics as their counterparts present on the outer membrane. This finding strongly suggests that newly synthesized transmembrane glycoproteins may freely diffuse to and from the inner nuclear membrane before entering into the intracellular transport pathway to the plasma membrane.